Comparative outcomes of holmium laser En bloc resection in superficial bladder tumors: Focus on operative time, catheterization, and hospital stay- A cross-sectional study. - Siddhartha, Thota; Jumde, Suvit (Student’s Journal of Health Research Africa, 2025)
Background In 2016, bladder cancer accounted for 186,000 fatalities and 437,000 new cases, making it the tenth most frequent cancer worldwide. The incidence of bladder urothelial carcinoma varies greatly by geography, with Eastern Europe and Asian nations having the lowest rates and Western Europe and North America having the greatest frequency. Objectives- The purpose of the study was to evaluate the results of holmium laser En Bloc resection for superficial bladder cancers. Materials and methods It was a cross-sectional, observational study. The study was carried out in the Department of Urology, Mahatma Gandhi Medical College and Research Institute, Puducherry, India. The study was conducted for one and a half years, that is, from December 2021 to Jun 2023. In all, 24 patients were enrolled. Patients over the age of 18 with superficial bladder cancer who intend to have their bladder tumors removed by transurethral resection (TURBT) at the Mahatma Gandhi Medical College and Research Institute in Puducherry within six months of receiving approval from the institutional ethics committee are included in this study. Results Nine patients (37.5%) had tumors in the right lateral bladder wall, while six patients (25%) had tumors in the posterior wall. Patients with multiple lesions used a larger median number of analgesic vials after surgery (2.00; IQR: 2.00–3.00) than patients with single lesions (1.00; IQR: 1.00–2.00). With a p-value of 0.017, this difference was statistically significant. Conclusion For the treatment of superficial bladder cancers, holmium laser en bloc excision is a secure and efficient method. In patients with single lesions, the method was linked to significantly lower analgesic requirements, shorter catheterization and hospital stays, and acceptable operative timeframes. Recommendations Further research, including larger-scale studies, is necessary to validate these observations and enhance the understanding of TURBT procedures’ efficacy and safety.